Islamic Moral Comedy? The Representation of Islam in Malaysian Comedy Films Syurga Cinta (Paradise of Love, 2009) and Ustaz, Mu Tunggu Aku Datang! (Ustaz, I’m Coming! 2013) - A.Rahman, Suria Hani; Sabran , Rosidayu; Hussin, Rosninawati (‘Abqari Journal, 2020)
This article examines how Islam is being represented in Malaysian comedy films: Syurga Cinta/Paradise of Love (Ahmad Idham, 2009) and Ustaz, Mu Tunggu Aku Datang!/Ustaz, I’m Coming! (Pierre Andre, 2013). As one of a popular genre in film, comedy and its comical narratives has the ability to critique social, cultural and political conditions within the specific context of Malaysia. Using film narrative analysis, this study identifies that both films revolve around a similar plot of a male quest for haram (forbidden) obsessions, such as fortune or women, and a return to morality (i.e. humility and true love). As these comedies attempt to illuminate the intersection between religion and comical narrative, the way they feature the main characters are not simply as sinful or immoral. Rather, they are portrayed as misguided, but equally amusing in dealing with misfortune and wrongfulness. This article found that the central element of both films lies in its incongruity between the traditional Islamic principle and trajectories which against morality. Besides the call for morality, this article also argues that Malaysian comedy is also shaped in response to the Islamisation of the public sphere, thus, underlines the ‘re-imagine social life’ within the Malay (sian)-Muslim context.